2005
DOI: 10.1007/s00203-005-0054-8
|View full text |Cite
|
Sign up to set email alerts
|

Betaine aldehyde dehydrogenase from Pseudomonas aeruginosa: cloning, over-expression in Escherichia coli, and regulation by choline and salt

Abstract: In the human pathogen Pseudomonas aeruginosa, betaine aldehyde dehydrogenase (BADH) may play a dual role assimilating carbon and nitrogen from choline or choline precursors--abundant at infection sites--and producing glycine betaine, which protects the bacteria against the high-osmolarity stress prevalent in the infected tissues. We cloned the P. aeruginosa BADH gene and expressed the BADH protein in Escherichia coli. The recombinant protein appears identical to its native counterpart, as judged by Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…The choline catabolic pathway and its regulation in P. aeruginosa have been described previously (20,22). Briefly, in P. aeruginosa the TetR family transcription factor BetI represses expression of betIBA and is derepressed by choline, allowing production of the BetA and BetB enzymes that convert choline into GB (39)(40)(41). The GATase 1-like AraC family transcription regulator (GATR) GbdR responds to GB and dimethylglycine (DMG) by inducing expression of catabolic genes, including gbcA-B, the dgc operon (PA5376, PA5377, dgcA, dgcB, PA5400, and PA5401), and the sarcosine oxidase genes, which together contribute to the sequential demethylation of GB to DMG, sarcosine, and finally glycine ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The choline catabolic pathway and its regulation in P. aeruginosa have been described previously (20,22). Briefly, in P. aeruginosa the TetR family transcription factor BetI represses expression of betIBA and is derepressed by choline, allowing production of the BetA and BetB enzymes that convert choline into GB (39)(40)(41). The GATase 1-like AraC family transcription regulator (GATR) GbdR responds to GB and dimethylglycine (DMG) by inducing expression of catabolic genes, including gbcA-B, the dgc operon (PA5376, PA5377, dgcA, dgcB, PA5400, and PA5401), and the sarcosine oxidase genes, which together contribute to the sequential demethylation of GB to DMG, sarcosine, and finally glycine ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has shown that P. aeruginosa betI and betB transcripts were particularly upregulated in CF patient lung infections, as well as burn wound samples, compared to those in planktonic controls (56). Because the betaine aldehyde dehydrogenase-encoding genes are responsible for the conversion of choline to GB (57), this implies choline uptake and utilization in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In most bacteria, one of the BCCT-family transporters is close to, and generally divergently transcribed from, the choline oxidase genes and its associated choline-responsive transcription factor (51-53). In P. aeruginosa, this transporter is named BetT1, and it is divergently transcribed from the betIBA operon, where betI encodes the BetI choline-responsive transcriptional repressor (53,54) (Fig. 2).…”
Section: Choline and Gb Import Versus De Novo Synthesismentioning
confidence: 99%
“…First, loss of BetI repression leads to betT1 induction (48), which provides for a higher rate of choline transport when choline remains in the extracellular environment. Second, loss of BetI repression stimulates transcription of betIBA, a single polycistronic transcript encoding the BetI repressor and the BetA and BetB enzymes for oxidation of choline to GB (52,53,89) (Fig. 2).…”
Section: Regulation Of Aerobic Choline and Gb Catabolism In Pseudomonadsmentioning
confidence: 99%